EDUKASI MANFAAT DAUN SINGKONG DAN DAUN PEPAYA SERTA PELATIHAN PENGOLAHANNYA MENJADI DENDENG SEBAGAI PANGAN ALTERNATIF UNTUK MENGUATKAN IMUN - Meyke Herina Syafitri (EDUKASI DAN PENGABDIAN MASYARAKAT, 2022)
Until now there is no specific treatment that has been proven to cure patients infected with the Covid-19 virus. The high number of positive confirmed cases of Covid-19 makes it is important to promote preventive efforts so as not to be infected with the virus. One thing that can be done is the fulfillment of nutrition, especially those that can support the immune system. Cassava leaves and papaya leaves have been shown to increase the immune response and reduce inflammation. The magnitude of the benefits possessed by cassava leaves and papaya leaves will be more felt by the community if they can be processed into a food that tastes good and is practical to serve. Based on this background, workshop is needed to process cassava leaves and papaya leaves turn into dendeng in order to support strengthening the family's immune system in the pandemic era. The training, which was conducted in the Kebonsari area of ??Surabaya, began with the providing of information using powerpoint and video media, followed by hands-on manufacturing practice. The dendeng produced is flat, has a soft texture, savory, and does not taste bitter. At the end of the event, an evaluation of the course of the training process was carried out through the provision of questionnaires. All participants stated that they were very satisfied with this activity and suggested that similar training could be carried out regularly in their neighborhood.